Analysis of community empowerment on projects sustainability: moderating role of sense of community - Ahmad, M.S. (Springer Netherlands, 2016)
Community led local development and community driven development played a mandatory role in rural development of both developed and under developed countries. The paper explores the relationship between community empowerment, sense of community and sustainability of community-driven projects. Looking at the record of social well at gross root level, very less attention was paid on development of deprived communities. Starting from the experience of community-driven organizations (i.e. the Citizen Community Boards in Pakistan), the paper attempts to answer two questions: (1) is there a relationship between community empowerment and project sustainability; and (2) is this relationship between community empowerment and project sustainability mitigated by the sense of community? Further, the paper elaborates on the concepts of “community empowerment”, “sustainability” and “sense of community”. A hierarchical regression analysis is used to test the relationship between community empowerment and sustainability of community-driven projects. This analysis highlights the central role of the sense of community in mitigating the relationship between community empowerment and sustainability. Community empowerment is significantly related to the sense of community. These relationships between sense of community, community empowerment and sustainability of community-driven projects are applicable to empowerment theory and measurement.